Qualitätsziele und Indikatoren für eine nachhaltige Mobilität. - Schäfer, Karl Heinz (Deutscher Verkehrs-Verl., 2006)
Nachhaltige Mobilität ist eine langfristig orientierte kommunale Vision. Ohne klar formulierte Zielsetzungen und wiederholte fundierte Überprüfung realisierter Zwischenschritte ist ein Erreichen dieser Vision kaum denkbar. Das Modellvorhaben "Mensch - Stadt - Verkehr - Umwelt" des Umweltbundesamts diente dazu, auf Grundlage der Erfahrungen in mehreren Modellstädten praxistaugliche Qualitätsziele und Indikatoren sowie einen Vorschlag zu deren Anwendung in der kommunalen Verkehrsentwicklungsplanung zu erstellen. difu

Quality targets and indicators for sustainable mobility. Based on a model project township-related quality targets and indicators have been devised for the areas of mobility and transport. The project lasted from early 2000 until mid-2004. Participating bodies included the communal agencies responsible for the environment, transport, town planning and development as well as citizens and local interest groups. By applying Agenda 21, the resultant concept covering mobility-related targets and indicators can be applied to other townships endeavours to creat high quality transport development plans. A comprehensive overview covers targets, indicators and guidelines for transport planning while a users' guide for communes offers advice with regard to the process of application. It also helps with the ascertainment of, and conversion to, township-related projects. difu
Keywords: Verkehr; Mobilität; Verkehrsplanung; Prognose; Verkehrsentwicklung; Verkehrsmittelwahl; Fahrradverkehr; ÖPNV; Indikator; Modell; Nachhaltigkeit; Verkehrsforschung; Qualitätsziel